2017
DOI: 10.1016/j.ecoenv.2017.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of imazethapyr-induced DNA oxidative damage by alkaline Endo III- and Fpg-modified single-cell gel electrophoresis assay in Hypsiboas pulchellus tadpoles (Anura, Hylidae)

Abstract: Imazethapyr (IMZT) is a selective postemergent herbicide with residual action. Available data analyzing its effects in aquatic vertebrates are scarce. In previous studies, we demonstrated that IMZT induces lesions into the DNA of Hypsiboas pulchellus tadpoles using the single-cell gel electrophoresis (SCGE) assay as a biomarker for genotoxicity. Currently, this assay can be modified by including incubation with lesion-specific endonucleases, e.g., endonuclease III (Endo III) and formamidopyrimidine-DNA glycosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 34 publications
0
10
0
2
Order By: Relevance
“…For instance, it has been found to cause oxidative stress and endocrine disruption in rats (Yang et al 2018) and developmental toxicity associated to thyroid dysfunction in zebrafish (Li et al 2020). Finally, imazethapyr has also been reported by causing metabolic alterations in Cyprinus carpio (Moraes et al 2011), genotoxicity in tadpoles of Rhinella arenarum and Hypsiboas pulchellus species (Carvalho et al 2019;Perez-Iglesias et al 2017;Perez-Iglesias et al 2015), and also in mammalian cells (Soloneski et al 2017); however, the toxicity of herbicide is poorly characterized and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been found to cause oxidative stress and endocrine disruption in rats (Yang et al 2018) and developmental toxicity associated to thyroid dysfunction in zebrafish (Li et al 2020). Finally, imazethapyr has also been reported by causing metabolic alterations in Cyprinus carpio (Moraes et al 2011), genotoxicity in tadpoles of Rhinella arenarum and Hypsiboas pulchellus species (Carvalho et al 2019;Perez-Iglesias et al 2017;Perez-Iglesias et al 2015), and also in mammalian cells (Soloneski et al 2017); however, the toxicity of herbicide is poorly characterized and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The conducted studies mainly focused on the evaluation of environmental stressors such as agrochemicals and heavy metals in vivo. [223,[227][228][229][230][231][232][233][234][235][236][237], fungicides (captan) [238], pesticides [239,240], antiparasitic agents [239], persistent organic pollutants (POPs) [219] as well as other agrochemicals [241] and poultry litter [242]. These studies indicated the DNA damaging effects of selected chemicals as well as using amphibians as sentinel organisms for the evaluation of environmental pollution.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The SCGE assay is a sensitive, rapid, and reliable method to determine DNA damage and can be considered as a nonspecific biomarker for genotoxicity of aquatic organisms (Vera‐Candioti et al 2013; Pérez‐Iglesias et al 2017). In our study, SCGE analysis revealed obvious DNA damage in all the fish samples and indicated that there were significant differences in DNA damage between fish samples from the Helong Reservoir and the controls from the upper reaches of the Liuxihe Reservoir ( p < 0.05); L. rohita was also the species most sensitive to DNA damage among the collected fish.…”
Section: Discussionmentioning
confidence: 99%